Mechanisms involved in the immunostimulation by probiotic fermented milk - Maldonado Galdeano, María Carolina (2009)
The intestinal ecosystem contains a normal microbiota, non-immune cells and immune cells associated with the intestinal mucosa. The mechanisms involved in the modulation of the gut immune system by probiotics are not yet completely understood. The present work studies the effect of a fermented milk containing probiotic bacterium Lactobacillus (Lb.) casei DN114001 on different parameters of the gut immune system involved with the nonspecific, innate and adaptive response. BALB/c mice received the probiotic bacterium Lb. casei DN114001 or the probiotic fermented milk (PFM). The interaction of the probiotic bacteria with the intestine was studied by electron and fluorescence microscopy. The immunological parameters were studied in the intestinal tissue and in the supernatant of intestinal cells (IC). Results showed that the probiotic bacterium interact with the IC. The whole bacterium or its fragments make contact with the gut associated immune cells. The PFM stimulated the IC with IL-6 release, as well as cells related to the nonspecific barrier and with the immune cells associated with the gut. This last activity was observed through the increase in the population of different immune cells: T lymphocytes and IgA+ B lymphocytes, and by the expression of cell markers related to both innate and adaptive response (macrophages). PFM was also able to activate the enzyme calcineurine responsible for the activation of the transcriptional factor NFAT. PFM induced mucosal immune stimulation reinforcing the non-specific barrier and modulating the innate immune response in the gut, maintaining the intestinal homeostasis.